Co-exposure to the food additives SiO2 (E551) or TiO2 (E171) and the pesticide boscalid increases cytotoxicity and bioavailability of the pesticide in a tri-culture small intestinal epithelium model: potential health implications. Issue 9 (15th August 2019) - Cao, Xiaoqiong; DeLoid, Glen M.; Bitounis, Dimitrios; De La Torre-Roche, Roberto; White, Jason C.; Zhang, Zhenyuan; Ho, Chin Guan; Ng, Kee Woei; Eitzer, Brian D.; Demokritou, Philip
Abstract : Widely used food-grade nanomaterials (TiO2 and SiO2 ) increase cytotoxicity, cellular uptake, and cellular translocation of co-ingested pesticide, boscalid. Abstract : Many toxicity investigations have evaluated the potential health risks of ingested engineered nanomaterials (iENMs); however, few have addressed the potential combined effects of iENMs and other toxic compounds ( e.g. pesticides) in food. To address this knowledge gap, we investigated the effects of two widely used, partly nanoscale, engineered particulate food additives, TiO2 (E171) and SiO2 (E551), on the cytotoxicity and cellular uptake and translocation of the pesticide boscalid. Fasting food model (phosphate buffer) containing iENM (1% w/w), boscalid (10 or 150 ppm), or both, was processed using a simulated in vitro oral-gastric-small intestinal digestion system. The resulting small intestinal digesta was applied to an in vitro tri-culture small intestinal epithelium model, and effects on cell layer integrity, viability, cytotoxicity and production of reactive oxygen species (ROS) were assessed. Boscalid uptake and translocation was also quantified by LC/MS. Cytotoxicity and ROS production in cells exposed to combined iENM and boscalid were greater than in cells exposed to either iENM or boscalid alone. More importantly, translocation of boscalid across the tri-culture cellular layer was increased by 20% and 30% in the presence of TiO2 and SiO2, respectively. One possible mechanism for this increase is diminished epithelial cell health, as indicated by the elevated oxidative stress and cytotoxicity observed in co-exposed cells. In addition, analysis of boscalid in digesta supernatants revealed 16% and 30% more boscalid in supernatants from samples containing TiO2 and SiO2, respectively, suggesting that displacement of boscalid from flocculated digestive proteins by iENMs may also contribute to the increased translocation.